Behavior of the Discharge Coefficient for the Overflow Characteristics of Oblique Circular Weirs - Emad Abdul Gabbar Al Babely (Tikrit Journal of Engineering Sciences, 2012)
This paper presents an experimental study and analysis for effect of the geometrical characteristics, of the oblique cylindrical weir on discharge coefficient, wherefrom three sizes used for the weir and two angles for the deviation. From the results, it was found that the coefficient of discharge is affected by geometrical characteristics represented by radius of the weir and the angle of inclination with the wall of the channel. It was noticed that the increase in the radius of the weir lead to a low discharge coefficient of the cylindrical weir. And found that discharge coefficient of the oblique weir is higher than the discharge coefficient of the normal weir. And the value of discharge coefficient is directly proportional with the weir inclination.